Drinking and Driving among University Students in 22 Low, Middle Income and Emerging Economy Countries - Karl PELTZER; Supa PENGPID (Tehran University of Medical Sciences, 2015)
Background: The aim of this study was investigate drinking, driving, and socio-behavioral factors among university students in low and middle income and emerging economy countries. Methods: Using anonymous questionnaires, data were collected from 18476 university students, of which 15151 (82.0%) were drivers of a car or motorcycle (41.3% men and 58.7% women), with a mean age of 20.7 years (SD=2.9), from 22 countries across Africa, Asia and Americas. Results: Overall, 17.3% reported to have been driving a car or motorcycle after having had too much to drink in the past 12 months, ranging from below 5% in Bangladesh, Indonesia and Kyrgyzstan to above 35% in China, Singapore and Thailand. In multivariate logistic regression analysis, among both men and women, earlier year of study, living in an upper middle income or high income country (OR=3.58, CI=3.00-4.27 and OR=2.95, CI=2.52-3.46), low intrinsic religiosity (OR=0.67, CI=0.54-0.83 and OR=0.34, CI=0.28-0.42), injury from motorcycle accidents (OR=4.29, CI=2.69-6.82 and OR=3.24, CI=2.26-4.63), and weak belief in the importance of not drinking (OR=1.78, CI=1.50-2.11 and OR=1.61, CI=1.37-1.88) and driving were associated with drinking and driving. Further, among men, older age (OR=1.04, CI=1.01-1.07), binge drinking (OR=1.53, CI=1.27-1.86) and illicit drug use (OR=1.22, CI=1.01-1.47), and among women, younger age (OR=0.95, CI=0.97-0.98), and a lower country BAC limit (OR=0.01, CI=0.001-0.18) was associated with drinking and driving. Conclusion: This study confirms low to high levels of drinking and driving in different cultures across Africa, Asia and the Americas. Various factors identified can be used to guide interventions to reduce drinking and driving among university students.   Keywords: Drink driving, Health behaviour, Health beliefs, University students, Multi-country